Ecological perspectives of ICT affordances in Malaysian higher education learning environment / Magdalina Jamian, Habibah Ab Jalil and Steven Eric Krauss - Krauss, Steven Eric (Faculty of Architecture, Planning and Surveying, 2013)
There is a continuous struggle on understanding learning settings, particularly with ICT integrations (i.e. incorporate the use of ICT in teaching and learning practice and environment). This paper aims to illuminate an alternative means of understanding virtual learning environment which is through affordances (perception-action coupling). Qualitative inquiry implemented in gathering participants’ experiences and perceptions regarding ICT integration in teaching practices through focus group discussion and semi-structured interviews. This study shows that preferences of ICT integration in a learning environment closely related to ICT affordances. Understanding of ICT affordances is indispensable in order to assessing conduciveness of learning environments with the ICT integrations.